(3GdJfejI aj YGde eJZjQ (B:s (3OQGSI aj eaghe GdJfejI heDTQGJgG (B/s - (3GdYjShj, GHQGgjes ((3GdbGgQI(B: s (3OGQ GdTQhb ddfTQ hGdJhRjY(B, s, 2001)
(3JWhQ eaghe GdJfejI(B- (3JWhQ eDTQGJ GdJfejI(B.s
Keywords: (3GdJfejIs; (3GdJfejI GdEbJUGOjIs; (3eDTQGJ GdJfejIs